Build and design case files handling application at Polres Jember - Dwi Yuniar Pradoko; Dewiyani Sunarto; Tony Soebijono (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Kepolisian Resort (Polres) Jember is the command structures of the Polri in the jember district. As for duty of the Polres regulation based on No 23 Tahun 2010/Bab 2/Paragraf 2/Pasal 5. Based on such regulation, Polres Jember cannot be separated from handling the docket and publishing a police record (SKCK). Many cases handled and many request publishing SKCK from people can effect the officers experiencing difficulty and required to work more quickly in doing their job. This is due to the absence of the applications that can help the performance of the Polres Jember officer.In this study, these problems solved by building case files handling application at Polres Jember using Systems Development Life Cycle (SDLC). Case file handling application that has built able to facilitate Polres Jember officer to handling the case files and publishing SKCK.After tested, case files handling application at Polres Jember can resolve the existing problems in accordance with the SOP Transparansi Di Bidang Penyidikan Sat Reskrim Polres Jember Tahun 2009 and Peraturan Kepala Kepolisian Negara Republik Indonesia Nomor 18 Tahun 2014 tentang Tata Cara Penerbitan Surat Keterangan Catatan Kepolisian. So this applications can manage and archive the case files, managing PUSINAFIS data, managing SKCK data, and can generate crime reports and SKCK reports.